2015
DOI: 10.1111/jcpe.12327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of access flap in the treatment of class II furcation defects. A systematic review and meta‐analysis of randomized clinical trials

Abstract: Teeth with mandibular class II furcation involvement treated with OFD show significant clinical improvements 6 months after surgery. Nevertheless, in order to better understand the magnitude of these changes and their clinical relevance, prospective long-term trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
(86 reference statements)
0
24
0
2
Order By: Relevance
“…45 Whether this CAL gain is clinically superior to the CAL gain obtained after open flap debridement surgery 47 remains debatable; In fact, in a systematic review with meta-analysis, Graziani and colleagues reported that open flap debridement in the treatment of degree 2 FI resulted in 0.55 mm CAL gain. 47 We found that the location of the treated furcation defect was shown to be highly associated with CAL gain at 1 year (Table 4). It was observed that compared to the buccal furcation of mandibular molars, the mid-facial, disto-palatal, and mesio-palatal furcations of upper molars were significantly associated with lower levels of CAL gain.…”
Section: Discussionmentioning
confidence: 83%
“…45 Whether this CAL gain is clinically superior to the CAL gain obtained after open flap debridement surgery 47 remains debatable; In fact, in a systematic review with meta-analysis, Graziani and colleagues reported that open flap debridement in the treatment of degree 2 FI resulted in 0.55 mm CAL gain. 47 We found that the location of the treated furcation defect was shown to be highly associated with CAL gain at 1 year (Table 4). It was observed that compared to the buccal furcation of mandibular molars, the mid-facial, disto-palatal, and mesio-palatal furcations of upper molars were significantly associated with lower levels of CAL gain.…”
Section: Discussionmentioning
confidence: 83%
“…Open flap debridement produces less clinical improvement with furcation lesions, comprising less than 1 mm of horizontal attachment gain, than with other types of periodontal defects (Fig. ) . Tunnel treatment of furcation defects is best performed at teeth with short root trunks, severe intrafurcal bone loss and wide root divergence, but may give rise to soft tissue resection .…”
Section: Surgical Treatment Of Periodontitismentioning
confidence: 99%
“…The performance of the different flaps included within the conservative periodontal surgery classification regarding intrabony defects has been thoroughly studied in a recent systematic review and meta‐analysis . This review included 27 trials with 12 months of follow up reporting on 647 subjects and 734 intrabony defects.…”
Section: Performance Of Surgical Intervention On Residual Pocketsmentioning
confidence: 99%
“… as: class I when horizontal loss of periodontal tissue support is < 3 mm; class II when horizontal loss is > 3 mm without encompassing the total width of the furcation; and class III when a horizontal through‐and‐through destruction of the periodontal tissue is present. The performance of open flap debridement in the surgical treatment of class II mandibular furcation defects is the subject of another systematic review from our group . Eleven randomized clinical trials with a minimum of 6 months of follow up were assessed.…”
Section: Performance Of Surgical Intervention On Residual Pocketsmentioning
confidence: 99%